Royal Book Lodge - Welchman, John C. (Berlin : Hatje Cantz, 2023)
Kiki de Montparnasse ; Péret, Benjamin ; Aragon, Louis ; Man Ray ; Éluard, Paul ; Hauser, Tobias ; Susin, Juli ; Bourgoin, Véronique ; Butzer, André ; Rumney, Ralph ; Riedel, Michael ; Loesch, Denis ; Schechinger, Niklas ; Parkina, Anna ; Pettibon, Raymond et al.
Renowned art historian John C. Welchman provides the first in-depth study of more than 30 years of creative activity by the Royal Book Lodge (RBL), a nimble and richly innovative network of international artists. Chapters examine the history and contexts of the RBL’s pathbreaking work in photography, video, ceramics, writing, artist’s books, archiving and collecting, and exhibition-making. Welchman discusses the leading ideas and practices of the formation as they have played out in the diverse cultural and political geographies of RBL affiliates and initiatives: narratives of displacement and migration; constructs of biography and fiction; notions of remote control; experiences and contestations of violence; and the RBL’s signal collaborations with the protagonists and legacy of the Situationist International. (from publisher)
Book with original lithograph by Kai Althoff
boek
Keywords: Royal Book Lodge